Not All Particles Are Equal: The Selective Enrichment of Particle-Associated Bacteria from the Mediterranean Sea - López-Pérez, Mario; Kimes, Nikole E.; Haro-Moreno, Jose M.; Rodriguez-Valera, Francisco (Frontiers in Microbiology, 2016)
We have used two metagenomic approaches, direct sequencing of natural samples and sequencing after enrichment, to characterize communities of prokaryotes associated to particles. In the first approximation, different size filters (0.22 and 5 μm) were used to identify prokaryotic microbes of free-living and particle-attached bacterial communities in the Mediterranean water column. A subtractive metagenomic approach was used to characterize the dominant microbial groups in the large size fraction that were not present in the free-living one. They belonged mainly to Actinobacteria, Planctomycetes, Flavobacteria and Proteobacteria. In addition, marine microbial communities enriched by incubation with different kinds of particulate material have been studied by metagenomic assembly. Different particle kinds (diatomaceous earth, sand, chitin and cellulose) were colonized by very different communities of bacteria belonging to Roseobacter, Vibrio, Bacteriovorax and Lacinutrix that were distant relatives of genomes already described from marine habitats. Besides, using assembly from deep metagenomic sequencing from the particle-specific enrichments we were able to determine a total of twenty groups of contigs (eight of them with >50% completeness) and reconstruct de novo five new genomes of novel species within marine clades (>79% completeness and <1.8% contamination). We also describe for the first time the genome of a marine Rhizobiales phage that seems infect a broad range of Alphaproteobacteria and live in habitats as diverse as soil, marine sediment and water column. The metagenomic recruitment of the communities found by direct sequencing in the large size filter and by enrichment had nearly no overlap. These results indicate that these reconstructed genomes are part of the rare biosphere which exists at nominal levels under natural conditions.